PENGARUH PENDIDIKAN KESEHATAN TENTANG DISMENORHEA TERHADAP PENINGKATAN PENGETAHUAN REMAJA PUTRI DI SMP MUHAMMADIYAH 2 GISTING KABUPATEN TANGGAMUS LAMPUNG TAHUN 2022: DISMENORHEA REMAJA - Dwi Restia Ningrum Dwi (Jurnal Maternitas Aisyah (JAMAN AISYAH), 2023)
ABSTRACT Dysmenorrhea is menstrual pain that occurs mainly in the lower abdomen that arises shortly before or with the start of menstruation and lasts for several hours or can last several days. The incidence of dysmenorrhea in adolescents ranges from 43% - 93%. This study aimed to determine the effect of health education on dysmenorrhea on increasing young women's knowledge at SMP Muhammadiyah 2 Gisting, Tanggamus Regency, Lampung, in 2002. This type of research is quantitative with a Pre-experimental design and a Group Pretest-Posttest Design. The population in this study were all female students at SMP Muhammadiyah 2 Gisting, Tanggamus Regency, totaling 58 students. Sampling in this study uses total sampling. The questionnaire as a research instrument was given during the pretest, followed by counseling. Then the post-test was given after 15 days of counseling—data analysis in research using the Wilcoxon test. The study's results showed an effect of health education on increasing knowledge of young women about dysmenorrhea with a p-value of 0.000 (p-value <α = 0.05). Based on the research that has been done, it can be suggested that health workers be able to provide health education on an ongoing basis using counseling, handouts, and audio-visual media. And for teenagers to be diligent in participating in youth posyandu. Keywords: Health Education, Knowledge, Dysmenorhea, Adolescents